Pelatihan dan Pengenalan Bahasa Pemrograman Dart di SMK TI Medan - Rahman, Maulia; Sinaga, Jenriko Sahat (Publikasi Pengabdian Masyarakat, 2022)
The use of Dart language in making android applications is a relatively easy programming language and in the world of work, the dart language has been commonly used so learning Darts from an early age is very beneficial for students. The problem faced by students at SMK Tritech Informatika Medan is how to make it easier for many students who are interested in entering college to master programming so that they graduate well. Studying computer science isn't just about learning technology, it's about learning logic, problem-solving, and creativity. Therefore, the solution to this research problem is to provide training on the Introduction and Training of Dart Programming Language which is easily understood by students in SMK for simple problems. Programming training in the form of interesting interactive introductions and hands-on exercises. From the results of the training, the trainees, students of SMK Tritech Informatika Medan, felt that this activity was very interesting and useful, as well as being able to improve understanding and skills in programming, IT, and its applications.